Discussion of the classification of pediatric drug clinical trials in children's hospitals in China - Yang, Yong; Jiang, Rui; Bai, Gengliang; Liu, Qingqing; Chen, Yongfa (Frontiers in Medicine, 2024)
Objectives：To gain insights into pediatric clinical trials conducted in children's hospitals in China, and provide valuable references for the development of children's hospitals as well as research and development of pediatric drugs. Methods：A comprehensive search was performed on the Chinese Clinical Trial Registry (Chi CTR) and ChinaDrugTrials.org.cn to collect information on all clinical trials involving subjects under 18 years old, including those conducted in children's hospitals. The retrieval period extended until December 31, 2022.Results：A total of 459 pediatric clinical trials were collected, comprising 299 from Chi CTR and 160 from the information platform. Postmarketing drug studies and phase III clinical trials accounted for the majority of research stages. These trials covered a wide range of diseases/systems, with a particular focus on respiratory system disorders, tumors, endocrine disorders, as well as nutritional or metabolic diseases. Chemical drugs constituted the most extensively studied category while traditional Chinese medicine/natural drugs received comparatively less attention. Geographically, clinical trial activities were primarily concentrated in eastern coastal regions of China with multi-center trials being predominant. Ethics committee approval was obtained for 427 studies. Conclusions：T Pediatric clinical trials conducted by children's hospitals in China have shown an overall upward trend; however, there is limited research focusing on traditional Chinese medicine along with significant regional and institutional imbalances observed. Furthermore, there is still room for improvement regarding ethical review processes. It is recommended that children's hospitals enhance their scientific research capabilities while optimizing resource allocation to meet medical service demands effectively. Additionally, fostering more investigative children's hospitals will contribute to promoting highquality development of children's health in China.